Tactile acuity, body schema integrity and physical performance of the shoulder: A cross-sectional study. (June 2016) - Botnmark, Ingunn; Tumilty, Steve; Mani, Ramakrishnan
Abstract: Background: Normative two-point discrimination thresholds (TPDTs) have been reported for different body regions and the relationships between TPDT and body schema integrity and physical performances are previously shown. However, such relationships with shoulder physical performance have not been investigated. Objectives: To quantify TPDT of the shoulders in healthy individuals and investigate whether TPDT and body schema integrity are related to physical performances and to identify the relationship between TPDT and body schema integrity. Design: Cross-sectional study. Results: Means (SD) of TPDTs of the dominant shoulder (DS) and non-dominant shoulder (NDS) were 44.8 (13.1) mm and 39.3 (9.5) mm respectively. TPDT scores were significantly negatively correlated with closed kinetic chain upper extremity stability test (CKCUEST) scores ( r  = −385, p  = .036) and left/right judgement task (LRJT) response times (DS: rho = −449, p  = .013 and NDS: rho = −388, p  = .034). No significant correlations were found between TPDT and scores on functional throwing performance index (FTPI) and LRJT accuracy. However, positive moderate correlations were observed between LRJT and CKCUEST scores. Conclusions: TPDTs for ND and NDS in a cohort of adults have been documented. Tactile acuity and body schema integrity scores were correlated with superior performance in the upper limb stability task, indicating the potential role of tactile acuity and motor imagery training on maximizing physical performance. Highlights: Reference values of shoulder tactile acuity have been reported. Non-dominant shoulder has better tactile acuity than the dominant shoulder. Tactile acuity of anterior, lateral, and posterior shoulder regions is similar. Better tactile acuity correlates with better performance in the stability task. Better body schema integrity correlates with better performance in the stability task.